2019
DOI: 10.4103/ijpvm.ijpvm_172_17
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the persian version of the “Multidimensional Assessment of Fatigue Scale”

Abstract: Background: Fatigue is a common symptom in office workers. The purpose of this study was to assess the psychometric properties of the Persian version of the Multidimensional Assessment of Fatigue (P-MAF) scale and its association with productivity among Iranian office workers. Methods: In order to validate the MAF scale, using “forward-backward” translation, cognitive debriefing, and cultural adaptation procedure, the English version of the MAF was translated into Farsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Military personnel with longer deployment duration reported more fatigue in this study, which agreed the positive relation between tenure and fatigue [21,22]. However, military personnel on the plateau did not complain more burnout over time, although the Pearson correlation between deployment duration and burnout was signi cant.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Military personnel with longer deployment duration reported more fatigue in this study, which agreed the positive relation between tenure and fatigue [21,22]. However, military personnel on the plateau did not complain more burnout over time, although the Pearson correlation between deployment duration and burnout was signi cant.…”
Section: Discussionsupporting
confidence: 84%
“…According to the above literature review, it is reasonable to speculate that there is an association between chronic exposure to HA and job burnout, and fatigue may play a mediating role in this process. More interestingly, previous study indicated that burnout and fatigue were positively related with tenure years [20][21][22]. Thus, the deployment duration at HA may have a moderating effect between altitude and fatigue as well as altitude and burnout.…”
Section: Introductionmentioning
confidence: 83%
“…Participants in the current study were asked to reflect upon their experiences with respect to fatigue within the past week. The psychometric properties of the P-MAF scale have been examined by Daneshmandi et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nurses in hospitals usually work in poor ergonomic working conditions for a long period of time, which can lead to an increase in MSDs, fatigue, and loss of efficiency [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants were asked to reflect upon their fatigue experiences within the last 7 days. The psychometric properties of the P-MAF were examined by Choobineh et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%